2007
DOI: 10.1086/518041
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofLeishmania (Viannia)Species on the Response to Antimonial Treatment in Patients with American Tegumentary Leishmaniasis

Abstract: Leishmania species can influence SbV treatment outcome in patients with CL. Therefore, parasite identification is of utmost clinical importance, because it should lead to a species-oriented treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
190
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(207 citation statements)
references
References 25 publications
8
190
1
8
Order By: Relevance
“…This observation was indeed pointed out in two other studies conducted in Peru where leishmania species were associated with different antimonial treatment outcomes. 10,11 This variation in cure rates has also been demonstrated in patients infected with L. ( V. ) braziliensis and L. ( V. ) guyanensis in Brazil where antimonial cure rates are lower than the ones reported in Bolivia and Peru. 9,12,13 Despite the epidemiologic importance of L. ( V. ) guyanensis in the Brazilian Amazon, only one clinical trial addressing treatment response of this leishmania species to antimonials was performed in the past 10 years.…”
Section: Introductionmentioning
confidence: 60%
“…This observation was indeed pointed out in two other studies conducted in Peru where leishmania species were associated with different antimonial treatment outcomes. 10,11 This variation in cure rates has also been demonstrated in patients infected with L. ( V. ) braziliensis and L. ( V. ) guyanensis in Brazil where antimonial cure rates are lower than the ones reported in Bolivia and Peru. 9,12,13 Despite the epidemiologic importance of L. ( V. ) guyanensis in the Brazilian Amazon, only one clinical trial addressing treatment response of this leishmania species to antimonials was performed in the past 10 years.…”
Section: Introductionmentioning
confidence: 60%
“…3,[15][16][17] Capture of sand flies and identification. Peridomiciliary sand fly specimens were captured in September, November, and December of 2009 (before and during the rainy season) in the vicinity of 10 arbitrarily selected houses during 10 consecutive days each month (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously demonstrated that at 12 months posttreatment, 30% of L. (V.) braziliensis-infected patients showed treatment failure with pentavalent antimony compared with 25% of L. (V.) peruviana-infected patients and 8% of L. (V.) guyanensis-infected patients, thus reiterating a species specificity to treatment response. 6 In Peru, where approximately 10,000 new cases of leishmaniasis are reported annually, 7 four species of the L.…”
Section: Introductionmentioning
confidence: 99%